INFLUENCIA DEL DETERIORO DEL CEPILLO DENTAL SOBRE LA HIGIENE ORAL DE LOS ADULTOS MAYORES (2010)
Objective: To determine the effect of the deterioration of the toothbrush on oral hygiene in the older population Elderly Welfare Center Juan Pablo II.Methods: A descriptive study of a prospective cohort of 45 people aged 60 or more was done. Related and clinical variables, teeth present in mouth, behavior when brushing, language coverage rate, quantified plaque index, prosthesis hygiene index and rate of deterioration of Rawls’s toothbrush and Col; functionality of the adult Barthel scale. In the test statistic analyzed the potential differences by chi-square test or Fisher exact test qualitative variables and t test for quantitative variables.Results: The percentage reductions in ratings of plaque achieved with a new toothbrush were significantly different from those obtained with three months of using toothbrushes. A both new and 3 month of use reduces plaque.Conclusion: By observing the deteriorating relationship between tooth brushing and oral hygiene of older adults found no relationship whatsoever. Therefore, the deterioration of the brush does not seem to influence the level of oral hygiene of adults.